DESIGN OF A WEB-BASED POSYANDU DATA MANAGEMENT APPLICATION WITH QR CODE SCANNING FOR PATIENT DATA IDENTIFICATION - Apridiansyah, Yovi; Marhalim; Juhardi, Ujang; Ikbal, Fikri (Antivirus : Jurnal Ilmiah Teknik Informatika, 2025)
This study discusses the design and development of a web-based Posyandu data management application integrated with QR Code scanning technology for patient data identification. The research background stems from data management problems in Posyandu that still rely on manual methods, leading to delays in data retrieval, duplication, recording errors, and information loss. The proposed solution is to build an integrated information system that utilizes QR Codes to accelerate patient identification processes and a centralized database to improve accuracy and efficiency in information management. The system development methodology includes requirements analysis, design using UML (Use Case, Activity, Sequence, and Class Diagrams), web-based application implementation, QR Code scanning integration, and functional testing using black box testing. Implementation results demonstrate that the system can facilitate rapid and structured management of child, pregnant mother, elderly, immunization, and visit data. The use of QR Codes has proven to accelerate data retrieval processes and reduce input errors, thereby improving the quality of health services in Posyandu. Black box testing results show all system features function with "Valid" status, confirming successful system implementation in meeting the operational needs of Posyandu Bungin Tambun, South Bengkulu.